Emotional regulation of students in following online learning: What are the implications of counseling? - Nurfarhanah, Nurfarhanah; Ceria, Puspa; Karina, Azmi Ade (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
Emotion regulation is a person’s ability to regulate, manage and respond to emotions according to the situation that occurs. Individuals who are able to manage emotions well will have a positive impact on their lives. This research was motivated by various problems experienced by students regarding emotional regulation in participating in online learning at the UNP Laboratory Development High School. Problems experienced by students include students who feel uncomfortable, bored, sad, annoyed, angry, anxious about tasks that have not been done, worried about learning outcomes, stress during online learning. This is because students cannot meet with friends and teachers, students do not understand the task to be done, students find it difficult to understand the subject matter given by the teacher and many assignments. One of the factors that influence emotion regulation is education. Through the education obtained, it is hoped that individual knowledge and knowledge will increase, so that individuals are able to regulate and manage emotions well. The aims of the study were to describe the emotional regulation of students in participating in online learning. This type of research is a descriptive research using quantitative methods. The population of this study were all students of UNP Laboratory Development High School, totaling 645 people. The research sample amounted to 247 people selected using proportional random sampling technique. The research instrument used was a Likert scale emotional regulation questionnaire. The results of the study revealed that overall students’ emotional regulation was in the good category 52.63 of students.